A pedra e a lei - Oscar de Vianna Vaz (2005)
The present work deals with the theme of freedom related to architecture, seeking to verify the limits of equivalence of both of these subjects. The chosen object here is the penitentiary, more specifically the ones located in the Belo Horizonte area, among which we included for a comparison the building that will be managed by APAC Associação de Proteção e Assistência ao Condenado (Association of Protection and Assistance to Convicts) in Santa Luzia. We started from Batallies statement related to the arché of architecture, which is by himself associated with the birth of penitentiaries. In the beginning we made abrief review of the history of prison. After that, we studied some of the main trends concerning contemporary penal treatment and their respective architectural solutions. In the same topic, we approached the situation in Brazil and some statistic data referring to the buildings we chose to analyze. The next chapter is dedicated to the study of each one of the penitentiary institutions. It was based on the research of documents, among which were architectural projects, specialized bibliography, visitation of the places, evaluation of photos and interviews with civil servants and the prisons employees. Because of security measures, the projects of the evaluated penitentiaries were not included in the corpus of this work, although we elaborated the spatial-syntactic map of the units whenever possible for us directly based on those projects. The map reveals relevant architectural aspects. Freedom isdealt with next, in a chapter in which we sought to distinguish the main lines of thought in the contemporary debate on this theme, connecting its derivations to the prison building and, in a broader way, to architecture. We also sought to investigate the effectiveness of analysis toolsused within the social function of architecture. In the end, we presented the results of our research and some considerations that aim to delimit the reach of our work and point some directions we didnt go into.